2021
DOI: 10.3389/fonc.2021.649338
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Glycosylation of Cancer Stem Cells and Targeting Strategies

Abstract: Cancer stem cell (CSCs) are deemed as one of the main reasons of tumor relapse due to their resistance to standard therapies. Numerous intracellular signaling pathways along with extracellular features are crucial in regulating CSCs properties, such as heterogeneity, plasticity and differentiation. Aberrant glycosylation of these cellular signaling pathways and markers of CSCs have been directly correlated with maintaining survival, self-renewal and extravasation properties. In this review, we highlight the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 163 publications
(183 reference statements)
0
16
0
1
Order By: Relevance
“…CSC-like features can be controlled in various ways. Post-transcriptional modifications, especially glycolsylation, have been reported to contribute significantly to CSC-like features in several cancers [19]. Glycosylation is a common post-translational modification of membrane-related and secreted proteins [20].…”
Section: Discussionmentioning
confidence: 99%
“…CSC-like features can be controlled in various ways. Post-transcriptional modifications, especially glycolsylation, have been reported to contribute significantly to CSC-like features in several cancers [19]. Glycosylation is a common post-translational modification of membrane-related and secreted proteins [20].…”
Section: Discussionmentioning
confidence: 99%
“…It has been well documented that aberrant glycosylation contributes to tumorigenesis in multiple cancer types [18][19][20]. In addition, aberrant glycosylation increased cancer stem cell ability for tumour proliferation [21] and also could weakened immune checkpoint blockade against cancer cells [22,23]. Simultaneously, accumulating data showed that protein glycosylation and trafficking were regulated by the conserved oligomeric Golgi (COG) complex [24].…”
Section: Discussionmentioning
confidence: 99%
“…As nicely summarized by Khan and Cabral, the aberrant glycosylation of markers of cancer stem cells (CSCs) in key cellular signaling pathways has been directly correlated with the self-renewal properties and drug-resistant mechanisms [135]. The Tian group performed site-specific N-glycoproteomics to characterize the differential N-glycosylation in MCF-7 cancer stem cells relative to MCF-7 cells, leading to the discovery of potential N-glycoprotein markers of MCF-7 cancer stem cells [30].…”
Section: Cancers and Other Diseasesmentioning
confidence: 99%